Best Practice of Halal Tourism Development in Various Countries: A Literature Review - Muhamad Azami Nasri (International Journal of Geotourism Science and Development, 2023)
Over the past few years, halal tourism has experienced rapid development worldwide. Halal tourism is present as a unique tourism concept and promotes Islamic law. Halal tourism also provides an accelerator for economic growth in a country. In addition, the projected presence of Muslim tourists will reach 140 million in 2023 and 160 million in 2024. Many countries with Muslim-majority populations are competing to develop halal tourism. However, until now, Indonesia, Malaysia, and Turkey have become the most competitive countries in developing world halal tourism according to the "halal tourist destination countries" event organized by the Global Muslim Travel Index (GMTI). In this event, Indonesia, Malaysia, and Turkey from 2019, 2021, and 2022 have always been the top 4 ranking countries. The purpose of this study is to analyze the development of halal tourism in Indonesia, Malaysia, and Turkey. This study's data sources came from journal articles, books, institutional publications, and websites. The results show that the development of halal tourism in Malaysia is still ahead of Indonesia and Turkey. This research uses a qualitative approach through a literature review on halal tourism in Indonesia and how it is practised in various countries. The main recommendation in this research is that the Indonesian government must focus on improving visitor visit aspects, sustainability, connectivity, and unique experiences in developing halal tourism. In addition, Indonesia, Malaysia, and Turkey need to maintain and improve the quality of halal tourism to become the best practice for developing halal tourism in various countries.